Pemberdayaan masyarakat melalui proses Cipta Tari inovatif di Lembaga Budaya Aceh Nusantara, Banda Aceh - Sabri Gusmail; Prasika Dewi Nugra; Benny Andiko (Unri Conference Series: Community Engagement, 2022)
The process of creating dance works cannot ignore motion as the main medium for expressing dance and music as supporting media. So that empirical experience is needed in the creative process including theoretical fundamental knowledge and practical abilities. The difficulty of creating innovative dance works originating from traditional arts has become a problem for several dance communities in Aceh, the tendency that often occurs is that the originality of the new works produced is doubtful. This is because the patterns of traditional dance movements are used without going through processing and so is the music accompaniment. This condition has a negative impact on the productivity of the community and traditional arts as objects of processing. The service partner is the Lembaga Buana with a priority on the problem of lack of insight and skills of human resources in creating innovative dances sourced from traditional arts, especially the use of digital audio technology as a stimulus for the creative process. In order to provide solutions to solving partner problems, service implementers will carry out knowledge and skills transfer activities in the use of digital audio workstation. The auditory stimulus is used as a stimulus in the process of creating innovative dance movement patterns in the community. The choice of solutions to respond to the development of digital technology and its use in dance. The form of activity includes training on the application of digital audio workstation in creating dance music and managing elements of dance movements. Methods for implementing activities include: planning, implementing, monitoring and, assessment. Applying project based learning models and performance assessment instruments in the implementation of training. The results of the written post test showed an increase in insight into the method of creating dance and musical accompaniment from an average value of 36.6 to 82.6 with a difference of 46. While the practice test showed an increase from 80% to 7% for poor criteria, 20% to 46% for good criteria and 0% to 47% for very good criteria. Service activities produce Intellectual Property Rights of registered sound or sound recordings entitled Kesatuan Bunyi with registration number 000390015.